Cognitive Function and its Risk Factors Among Older US Adults Living at Home. Issue 3 (July 2018) - Dale, William; Kotwal, Ashwin A.; Shega, Joseph W.; Schumm, L. Philip; Kern, David W.; Pinto, Jayant M.; Pudelek, Kelly M.; Waite, Linda J.; McClintock, Martha K.
Abstract : Background: The Montreal Cognitive Assessment (MoCA) has not been administered to a representative national sample, precluding comparison of patient scores to the general population and for risk factor identification. Methods: A validated survey-based adaptation of the MoCA (MoCA-SA) was administered to a probability sample of home-dwelling US adults aged 62 to 90, using the National Social Life, Health, and Aging Project (n=3129), yielding estimates of prevalence in the United States. The association between MoCA-SA scores and sociodemographic and health-related risk factors were determined. Results: MoCA-SA scores decreased with age, and there were substantial differences among sex, education, and race/ethnicity groups. Poor physical health, functional status, and depression were also associated with lower cognitive performance; current health behaviors were not. Using the recommended MoCA cut-point score for Mild Cognitive Impairment (MoCA score <26; MoCA-SA score <17), 72% (95% confidence interval, 69% to 74%) of older US adults would be classified as having some degree of cognitive impairment. Conclusions: Our results provide an important national estimate for interpreting MoCA scores from individual patients, and establish wide variability in cognition among older home-dwelling US adults. Care should be taken in applying previously-established MoCA cut-points to the general population, especially when evaluating individuals from educationally and ethnically diverse groups. Abstract : Supplemental Digital Content is available in the text.